PENGARUH DIAMETER PIPA NOZZLE PADA KINERJA TURBIN AIR PELTON SKALA LABORATORIUM - Syaief, Adhiela Noer; Isworo, Hajar; Ivana, reza Taufiqi; Putra, Muhammad Rezki Fitri; Yasin, Muhammad Noor (POLITALA PRESS, 2024)
Pelton turbine is an energy conversion medium that utilizes flow performance as a driver and produces electrical energy due to the conversion of turbine rotation. The turbine works when the turbine nozzle injects flow towards the tip of the nozzle which leads directly to the inlet surface of the turbine blade. In this research, we know the effect of nozzle diameter on the performance of turbines that produce different electrical power from various parameters, namely: nozzle diameter used; 1